MENAKAR KEADILAN PAJAK PENGHASILAN DAN INSENTIF BAGI UMKM DI MASA PANDEMI COVID-19 - Arief Budi Wardana (JURNAL PAJAK INDONESIA, 2021)
SMEs are one of the elements of the economy affected by the Covid-19 pandemic. This study wants to see the impact of the pandemic on the SME's business cycle, as well as to measure the tax equity in the implementation of income tax along with the incentives provided. This study uses a narrative approach in a qualitative corridor based on the data obtained from interviews. As a result, the impact of the pandemic on SMEs varies greatly depending on the type and strategy of the business. This diversity erodes tax equity in terms of income tax and its incentive specified to SMEs. To overcome the tax equity issue, both professional dan academic sectors need to disseminate accounting for SMEs during the transition.